2017
DOI: 10.24200/sci.2017.4240
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric energy harvesting from vertical piezoelectric beams in the horizontal fluid flows

Abstract: Abstract. Piezoelectric Energy Harvesting (PEH) of uid-ow energy has attracted signi cant attention throughout the last decade. In the previous PEH from uid ow, a piezoelectric beam was placed behind a blu body, such as circular cylinders. Hence, the piezoelectric beam oscillated due to the vortex shedding behind of the blu body. Subsequently, this vibration generated voltage in the beam. In many engineering vehicles such as airplanes, the strong vortex shedding caused by blu body was destructive and reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…As a result of turbulence created around and in the wake of the cylinder, the piezoelectric beam could vibrate in the direction normal to the flow, and it was shown that 0.035 mW of average power could be generated at a wind speed of 5 m s −1 . Similar results were found by Amini et al in 2017 [340] for a comparable piezoelectric device.…”
Section: Harvesting Of Airflow Using Flutter-style Harvesterssupporting
confidence: 91%
“…As a result of turbulence created around and in the wake of the cylinder, the piezoelectric beam could vibrate in the direction normal to the flow, and it was shown that 0.035 mW of average power could be generated at a wind speed of 5 m s −1 . Similar results were found by Amini et al in 2017 [340] for a comparable piezoelectric device.…”
Section: Harvesting Of Airflow Using Flutter-style Harvesterssupporting
confidence: 91%
“…[11][12][13][14][15][16][17] Fluid flow ubiquitously exists in the environment and could be converted to structural vibrations. 18,19 Based on the mechanism of flow-induced vibration, researchers have proposed various aeroelastic PEHs. 20,21 Amini et al 22 presented an accurate numerical method for modelling a PEH placed in fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid flow ubiquitously exists in the environment and could be converted to structural vibrations . Based on the mechanism of flow‐induced vibration, researchers have proposed various aeroelastic PEHs .…”
Section: Introductionmentioning
confidence: 99%
“…The flow-induced vibration is often used as an energy source for piezoelectric energy harvesters. Amini et al [15] proposes a piezoelectric vertical beam with attached end cylinder as an energy harvester in the lowspeed flows. Piezoelectric energy harvesters based on vortexinduced vibration and galloping [16][17][18][19] have been extensively studied in the past several years.…”
Section: Introductionmentioning
confidence: 99%